REE, BA, SR AND NA CARBONATES IN MIASKITES OF THE ILMENOGORSKY BLOCK (SOUTH URALS) - E.P. Makagonov; V.A. Kotlyarov (Минералогия)
The REE, Ba, Sr and Na carbonates (ankilite-(Ce), barytocalcite, burbankite, dawsonite, strontianite and ewaldite) were identified in miaskites of the Ilmenogorsky block (South Urals). Barytocalcite, burbankite, dawsonite and ewaldite were found for the first time in the Ilmenogorsky miaskite block. The chemical composition of the minerals is as follows (wt. %): ankilite-(Ce) – SrO 18.1–19.7, CaO 1.24–2.52, REE oxides 47.41–50.53 (La/Ce ratio 0.40–1.00); barytocalcite – CaO 18.18–19.10, BaO 51.38–52.06; burbankite – Na2 O 10.35–15.44, CaO 2.41–10.93, SrO 14.8–41.3, BaO 0–9.76, REE oxides 1.16–18.65 (La/Ce ratio 0.57–1.04), traces of Y, K, Fe; dawsonite – Al2 O3 38.50, Na2 O 19.76; strontianite (average of 11 analyzes) – SrO 66.79, CaO 2.92; ewaldite – BaO 36.10–36.84, SrO 8.55–8.88, Na2 O 5.51–5.84, CaO 4.94–5.11, Y2 O3 8.41–8.80, traces of Dy, Gd, Er, Th. The composition of carbonates is typical of those from alkaline carbonatite complexes. The morphology and assemblages of carbonates in miaskites indicate their formation at the final stages of evolution of the alkaline complex with participation of aqueous-carbonic fluid.